Methimazole-Related Substances: Structural Characterization and In Silico Toxicity Assessment - Leo Štefan; Ivica Đilović; Lara Saftić Martinović; Robert Vianello; Ana Čikoš (Crystals)
The continuous tightening of pharmaceutical regulations forces drug manufacturers to unambiguously characterize the substances related to the active pharmaceutical ingredients (API). Here, we report the synthesis, complete spectroscopic, chromatographic, thermal and computational characterization, as well as in silico prediction of bacterial mutagenicity for two previously reported but never fully characterized impurities of methimazole. Additionally, their structures were analyzed by single-crystal X-ray diffraction. 1-Methyl-(2-methylthio)-1H-imidazole also known as methimazole impurity C, was obtained mainly in the form of the iodide salt (C5H9IN2S) crystallizing in monoclinic space group P21/c. The disulfide (2,2′-disulphanylbis(1-methyl-1H-imidazole)), C8H10N4S2) was obtained in yellow form crystallizing in the monoclinic C2/c space group.